Fabrication and Characterization of Ta–GelMA–BG Scaffolds by Chemical Crosslinking Processing for Promotion Osteointegration - Zhao, Fujian; Ji, Xiongfa; Yan, Yang; Yang, Zhen; Chen, Xiaofeng; Ma, Limin (Frontiers in Materials, 2021)
The repair of bone defects in load-bearing position still faces great challenges. Tantalum (Ta) has attempted to repair bone defects based on the excellent mechanical properties. However, the osseointegration of Ta remains to be improved due to the lack of osteoinduction. Herein, tantalum-gelatin methacryloyl-bioactive glass (Ta-GelMA-BG) scaffolds were successfully fabricated by loading BG in 3D-printed Ta scaffolds through a chemical crosslinking method. The results showed that the composite scaffolds have the ability to promote cell adhesion and proliferation. The incorporation of BG resulted in a significant increase in apatite-forming and osteogenesis differentiation abilities. In vivo results indicated that the Ta-GelMA-BG scaffolds significantly enhance the osteointegration at the early stage of implantation. Overall, the Ta-GelMA-BG scaffolds are a promising platform for load bearing bone regeneration field.